Organizational Disalignment and Normative Tension in Multicultural Work Environments: A Review of Value Conflict Mechanisms - Irfan, Mochamad (Journal of Social Science Studies, 2023)
This literature-based study investigates how value conflicts emerge and manifest within multicultural organizational environments. Drawing on research from intercultural management, cross-cultural psychology, and organizational behavior, the analysis reveals that such conflicts arise from deeply embedded differences in normative systems related to leadership, communication, time orientation, authority, and ethical reasoning. These divergences influence how individuals interpret organizational expectations, interpersonal interactions, and institutional legitimacy. The review identifies specific sites where value misalignment becomes visible, including performance evaluation, feedback mechanisms, team rituals, and policy design. Furthermore, it highlights how unacknowledged value conflicts contribute to relational disengagement, perceived injustice, and latent resistance. Through critical examination of power dynamics, institutional responses, and cultural symbolism, the study shows that value conflict is not merely a matter of interpersonal tension but a structural phenomenon with significant implications for organizational sustainability. The findings advocate for more reflexive, inclusive, and pluralistic approaches to policy and leadership in culturally complex settings. Ultimately, the study provides a theoretical and practical framework for understanding the relational architecture of value-based conflict in diverse institutions.